EKSISTENSI UNDANG.UNDANG NOMOR. 32 TAHUN 2OO4 TENTANG PEMERINTAHAN DAERAH - Mohamad Yuhdi Batubara (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2012)
LawNo.32Year2004 onRegionalGovernment is the elaboration and implementation of the provisions of Article I 8 paragraph (2) of the Constitution of 1945 which determined that the area set up and manage their own affairs in accordance with the principle of autonomy and assistance. This law does not need to be revised. On the other hand, this law has to be maintained in practice because thisactual law has been set up all aspects oflocal governance/decentralization.